2010
DOI: 10.1038/ijo.2010.217
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic and genetic variation in leptin as determinants of weight regain

Abstract: Aims: Over 75% of obese subjects fail to maintain their weight following weight loss interventions. We aimed to identify phenotypic and genetic markers associated with weight maintenance/regain following a dietary intervention. Subjects and methods: In the 2-year Dietary Intervention Randomized Controlled Trial, we assessed potential predictors for weight changes during the 'weight loss phase' (0-6 months) and the 'weight maintenance/regain phase' (7-24 months). Genetic variation between study participants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
1
51
0
1
Order By: Relevance
“…The fact that higher baseline plasma levels seemed to predict weight regain had been reported before [13]. Further, in a study with a weight loss phase of 6 months and a follow-up of 7–24 months, Erez et al [49 ]showed that weight regain was predicted by a relatively strong decrease in weight together with a decrease in leptin. On the other hand, conflicting findings have been reported as well.…”
Section: Module 2: Energy Regulation By Metabolic Hormonesmentioning
confidence: 65%
“…The fact that higher baseline plasma levels seemed to predict weight regain had been reported before [13]. Further, in a study with a weight loss phase of 6 months and a follow-up of 7–24 months, Erez et al [49 ]showed that weight regain was predicted by a relatively strong decrease in weight together with a decrease in leptin. On the other hand, conflicting findings have been reported as well.…”
Section: Module 2: Energy Regulation By Metabolic Hormonesmentioning
confidence: 65%
“…Strong hormonal influences drive weight regain after weight loss 26 , and the individual variation in this process has yet to be characterised. However associations between success of initial weight loss and baseline leptin levels have been demonstrated 27 . Many genes may be involved in causing and/or promoting obesity and so it is not unexpected that the phenotypic presentation and response to treatments may vary substantially 28 .…”
Section: Discussionmentioning
confidence: 99%
“…HOMA-IR was calculated according to the following equation (22): insulin (lU/mL) · fasting glucose (mmol/L)/ 22.5. Details of the methods were described previously (23).…”
Section: Clinical and Laboratory Characteristicsmentioning
confidence: 99%